2022
DOI: 10.1111/jth.15804
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ADAMTS13‐independent VWF regulation in sickle cell disease

Abstract: Background: Von Willebrand factor (VWF) is elevated in sickle cell disease (SCD) and contributes to vaso-occlusion through its thrombogenic properties. VWF is regulated by ADAMTS13, a plasma protease that cleaves VWF into less bioactive multimers.Independent investigations have shown VWF to be elevated in SCD, whereas measurements of ADAMTS13 have been variable. Objectives:We assessed ADAMTS13 activity using multiple activity assays and measured levels of alternative VWF-cleaving proteases in SCD. Methods/ Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Although there still remain gaps in our general understanding of the factors that dysregulate this pathway, particularly with respect to ADAMTS13 inhibition, as studies have recently reported additional inhibitory mechanisms. While there exists ADAMTS13-independent proteolytic pathways that increase in SCD patients to regulate VWF, such as neutrophil and endothelial-derived proteases and matrix metalloproteinase 9, their activity is not sufficient in mitigating the VWF burden in SCD [ 28 ▪▪ ]. Notably, studies have demonstrated that the gold standard treatment for SCD, hydroxyurea, does not prevent the dysregulation of the VWF - ADAMTS13 axis in SCD, leaving patients still susceptible to its downstream complications [ 29 ▪ ].…”
Section: Von Willebrand Factor and Its Role In Sickle Cell Disease Pa...mentioning
confidence: 99%
“…Although there still remain gaps in our general understanding of the factors that dysregulate this pathway, particularly with respect to ADAMTS13 inhibition, as studies have recently reported additional inhibitory mechanisms. While there exists ADAMTS13-independent proteolytic pathways that increase in SCD patients to regulate VWF, such as neutrophil and endothelial-derived proteases and matrix metalloproteinase 9, their activity is not sufficient in mitigating the VWF burden in SCD [ 28 ▪▪ ]. Notably, studies have demonstrated that the gold standard treatment for SCD, hydroxyurea, does not prevent the dysregulation of the VWF - ADAMTS13 axis in SCD, leaving patients still susceptible to its downstream complications [ 29 ▪ ].…”
Section: Von Willebrand Factor and Its Role In Sickle Cell Disease Pa...mentioning
confidence: 99%
“…ADAMTS-13 independent cleavage of VWF has also been found in SCD patient plasma [55], opening the possibility that other proteases, such as matrix metallopeptidase 9, could play a role in VWF processing.…”
Section: Endothelial Von Willebrand Factor: the Invisible Stringmentioning
confidence: 99%
“…A double-blind, placebo-controlled, phase I clinical trial, called rADAMST-13 in Sickle Cell Disease (RAISE), is enrolling adult SCD patients (NCT 03997760) and will investigate the effect of rADAMTS13 on disease severity markers. ADAMTS-13 independent cleavage of VWF has also been found in SCD patient plasma [55], opening the possibility that other proteases, such as matrix metallopeptidase 9, could play a role in VWF processing.…”
Section: Andand 54mentioning
confidence: 99%
“…Usually, the number of acute episodes tends to increase with age, and more than 50% of adults with SCD suffer from persistent chronic pain [ 11 ]. Leukocyte activation, oxidative stress, and ischemia/reperfusion are some factors specific to SCD that can trigger endothelial activation and lead to the development of VOC episodes [ 12 ]. Following the endothelial activation, nitric oxide bioavailability is impaired, and a variety of endothelial adhesion molecules are expressed (e.g., VCAM-1, selectins, ICAM-1), which will affect both the macro- and microvasculature [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leukocyte activation, oxidative stress, and ischemia/reperfusion are some factors specific to SCD that can trigger endothelial activation and lead to the development of VOC episodes [ 12 ]. Following the endothelial activation, nitric oxide bioavailability is impaired, and a variety of endothelial adhesion molecules are expressed (e.g., VCAM-1, selectins, ICAM-1), which will affect both the macro- and microvasculature [ 12 , 13 ]. Even at steady state, SCD subjects have elevated levels of these adhesion molecules compared with controls, and it was reported a further increase during VOC episodes, suggesting a key involvement [ 4 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%